Targeting the Cancer-Stroma Interaction: A Potential Approach for Pancreatic Cancer Treatment - Li, Xuqi (2012)
Recent studies have demonstrated that the interaction between the cancer and the stroma, play a key role in the development of pancreatic cancer. The desmoplasia, which consists of fibroblasts, pancreatic stellate cells, lymphatic and vascular endothelial cells, immune cells, pathologic increased nerves, and the extracellular matrix (ECM), creates a complex tumor microenvironment that promotes pancreatic cancer development, invasion, metastasis, and resistance to chemotherapy. Thus, the potential approach for targeting the components of this desmoplastic reaction or the pancreatic tumor microenvironment might represent a novel therapeutic approach to advanced pancreatic carcinoma. Novel therapies that target on the pancreatic tumor microenvironment should become one of the more effective treatments for pancreatic cancer.